documenta - Dokumente 1955-1968 : Vier internationale Ausstellungen moderner Kunst - Texte und Fotografien. - Westecker, Dieter; Eberth, Carl; Lengemann, Werner; Müller, Erich (Kassel : Georg Wenderoth Verlag, 1972)
Alechinsky, Pierre ; Andre, Carl ; Antes, Horst ; Appel, Karel ; Arp, Hans (Jean) ; Bacon, Francis ; Barlach, Ernst ; Beckmann, Max ; Bill, Max ; Bontecou, Lee ; Brancusi, Constantin ; Brüning, Peter ; Butler, Reginald ; Calder, Alexander ; César ; Chadwick, Lynn ; Chagall, Marc ; De Chirico, Giorgio ; Christo ; Delvaux, Paul ; Dubuffet, Jean ; Riverhead (New York) ; Francis, Sam ; Frankenthaler, Helen ; Geiger, Rupprecht ; Geldmacher, Klaus ; Gentils, Vic ; Gonzales, Julio ; Gorky, Arshile ; Hajek, Otto Herbert ; Hauser, Erich ; Held, Al ; Herbin, Auguste ; Hiltmann, Jochen ; Hofer, Karl ; Indiana, Robert ; Ipousteguy, Jean ; Jensens, Alfred ; Kandinsky, Wassily ; Kienholz, Edward ; Kirchner, Ernst Ludwig ; Klapheck, Konrad ; König, Fritz ; Kramer, Harry ; Kricke, Norbert ; Lardera, Berto ; Laurens, Henri ; Leger, Fernand ; Lehmann, Kurt ; Lehmbruck, Wilhelm ; Lenk, Thomas ; LeWitt, Sol ; Lichtenstein, Roy ; Lipchitz, Jacques ; Lipton, Seymour ; Louis, Morris ; Mack, Heinz ; de Maria, Walter ; Marini, Marino ; Mariotti, Francesco ; Marisol, Escobar ; Matisse, Henri ; Megert, Christian ; Metcalf, James ; Mettel, Hans ; Miro, Joan ; Moore, Henry ; Morlotti, Ennio ; Morris, Robert ; Müller, Robert ; Nay, Ernst Wilhelm ; Nele, E.R. ; Nolde, Emil ; Oldenburg, Claes ; Paolozzi, Eduardo ; Pasmore, Victor ; Pevsner, Antoine ; Picasso, Pablo ; Pistoletto, Michelangelo ; Pollock, Jackson ; Rauschenberg, Robert ; Rebeyrolle, Paul ; Reichert, Josua ; Rickey, George ; Roeder, Emy ; Rosenquist, James ; Rouault, Georges ; Schultze, Bernard ; Schumacher, Emil ; Segal, George ; Smith, David ; Smith, Richard ; Sonderborg, K.R.H. ; Soulages, Pierre ; Stadler, Toni ; de Staël, Nicolas ; Stella, Frank ; Suvero, Mark di ; Tajiri, Shinkichi ; Tomlin, Bradley Walker ; etc.
Duits
boek